Analisis Kesulitan Belajar Siswa SMA dalam Pembelajaran Matriks: Systematic Literature Review - Hamid, Abdurahman; Asmaun, Asmaun; Alimuddin, Fauziyyah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
This aims of study are to analyze senior high school students’ learning difficulties in matrix topics and to identify their causal factors and potential instructional solutions through a Systematic Literature Review (SLR). Research on matrix learning difficulties is urgent, as matrices constitute a foundational topic for advanced mathematical concepts and their applications across various disciplines, yet many students continue to demonstrate persistent conceptual and procedural challenges. A total of 13 peer-reviewed articles published between 2014 and 2024 were systematically selected and analyzed based on three main focuses: types of learning difficulties, contributing factors, and recommended learning strategies. The findings indicate that students commonly experience difficulties in four aspects: understanding basic matrix concepts, performing matrix operations, solving contextual problems, and interpreting and constructing matrices from word problems. These difficulties are influenced by internal factors such as low mathematical ability and learning motivation, as well as external factors including social environment, limited instructional resources, and family economic conditions. This study recommends strengthening conceptual understanding, providing systematic operational practice, integrating visual learning media, and offering additional instructional support for students with limited learning resources. The results provide valuable insights for teachers, curriculum developers, and researchers to improve the quality of matrix learning at the secondary school level.